2006
DOI: 10.1097/01.mib.0000194182.85047.6a
|View full text |Cite
|
Sign up to set email alerts
|

Educate, communicate, anticipate-practical recommendations for transitioning adolescents with IBD to adult health care

Abstract: The cyclical nature of chronic illness requires that children with inflammatory bowel disease be transitioned to the adult medical system with as much continuity of care as possible. Transition from pediatric to adult medical care continues to present significant barriers. The philosophy of transition centers on a process, with the actual transfer to adult care as a point along this clinical pathway. Concrete steps can be taken to help patients prepare for new responsibilities. The aim of this review is to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
7

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 10 publications
2
85
0
7
Order By: Relevance
“…The perceived lack of information about AHC may be due to the failure of transition planning. Transition protocols that include guidance about appropriate levels of information to be provided to adolescents and parents at regular intervals could be helpful in starting early enough with provision of information and by supporting autonomy and self-responsibility as the basis to develop/build a well-planned time schedule for a smooth transfer [9,21,22]. However, a recent study from Australia showed that a documented transition plan was available only among 13% of young adults older than 18 years and treated at a pediatric hospital [11] providing evidence of failure of transition planning.…”
Section: Discussionmentioning
confidence: 99%
“…The perceived lack of information about AHC may be due to the failure of transition planning. Transition protocols that include guidance about appropriate levels of information to be provided to adolescents and parents at regular intervals could be helpful in starting early enough with provision of information and by supporting autonomy and self-responsibility as the basis to develop/build a well-planned time schedule for a smooth transfer [9,21,22]. However, a recent study from Australia showed that a documented transition plan was available only among 13% of young adults older than 18 years and treated at a pediatric hospital [11] providing evidence of failure of transition planning.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians must be sensitive to this transition and the barriers it may present. It has been recommended that the child be approached from the commonly accepted developmental stages, roughly defined chronology by ages 11-13, 14-16, 17-19, and 20-23 [52] . These are certain traits needed to make a successful transition of care and allow for the ability to navigate through the adult healthcare milieu.…”
Section: Transition Of Carementioning
confidence: 99%
“…The transition process should therefore consist of a stepwise programme with ageappropriate checklists of tasks for the patient, as well as for the medical team. 3,8,9 Currently, there are no tools to evaluate the effect of different IBD transition programmes. 9 In 2006, a transition clinic for IBD patients between 14 and 18 years was initiated in the Erasmus MC -Sophia Children's Hospital.…”
Section: Introductionmentioning
confidence: 99%